DFT Study of Diluted Magnetic Semiconductor Cd1-xCrxS at x=3.125%. (2016) - Rani, Anita; Kumar, Ranjan
Abstract: We investigate the structural, Electronic and Magnetic properties of Cd1-xCrxS diluted Magnetic Semiconductor (x=0.03125) in Zinc Blende (B3) phase. The calculations have been performed using Density functional theory as implemented in the Spanish Initiative for Electronic Simulations with Thousands of Atoms code using local density approximation as exchange-correlation (XC) potential. Calculated electronic band structures and magnetic properties of Cd1-xCrxS are discussed in terms of contribution of Cr 3d5 4s1, Cd 4d10 5s2, S 3s2 3p4 orbital's. Study of band structures shows half-metallic ferromagnetic nature of Cd1-xCrxS. The calculated values of s-d exchange constant Nα and p-d exchange constant Nβ shows the magnetic nature of these compounds.